Pengaruh Citra Merek dan Kualitas Layanan Terhadap Minat Kunjung Pembeli CV.88 Auto Motor Surabaya - Siti Wisnu Laili (Journal of Islamic Economics and Finance, 2024)
This study aims to determine the influence of brand image and service quality, on the interest in visiting CV.88 Auto Motor Surabaya. The sample in this study was 100 respondents taken using accidental sampling technique with the slovin formula. The data analysis technique uses multiple linear regression. The results showed that brand image and service quality partially affect the interest of CV.88 Auto Motor Surabaya buyers as evidenced by the results of the t test, namely the significance value of the brand image variable (X1) 0.012 < 0.05,. In the service quality variable (X2) the significance value is 0.000 < 0.05,. This shows that all independent variables of brand image, and service quality have a partial effect on buyer visitor interest. The test results simultaneously show that brand image, and service quality simultaneously affect the interest of CV.88 Auto Motor Surabaya buyers as evidenced by the F test results which show a significance value of 0.000 < 0.05. While the test results in the coefficient of determination (R2) show that brand image, and service quality have a major influence on buyer visit interest by 64.8% while the remaining 35% (100% - 64.8%) are influenced by other variables outside the study